Espiritualidade quântica?: consciência, religião e ciência no pensamento de Amit Goswami - Nogueira, Pablo (2010)
The objective of this dissertation is to discuss the religious elements in the work of Indian physicist Amit Goswami. Goswami became a familiar figure in the New Age movement because of his proposal to interpret quantum mechanics −based on the idea of a non-local and transcendent conscience as the foundation of reality − and for his advocacy of a synthesis between spirituality and scientific discourse. The text begins with a history of connections between science and religion proposed since the mid 19th century until the rise of New Age in the 1970s. Its main focus is the dialogue between science and religion which began to be settled with the development of quantum mechanics. The dissertation approaches the work of Goswami with the intent of highlighting its main ideas: the criticism of materialist realism, the mystical origin of religions, their inability to adequately convey the essential truth of the mystical experience, his confidence that certain experiments could support the belief in a transcendent dimension of reality and the moral crisis experienced by modern societies. Next, the dissertation uses the definition of religion proposed by Geertz and makes evident the religious element of Goswami´s speech characterized by its quest to link cosmology and ethos in order to substantiate a new ethic for contemporary societies. Finally, Hanegraaff´s definitions of spirituality and religion allow distinguish his Goswami s work as an example of spirituality based on a secular symbolic system